2018
DOI: 10.1111/evo.13519
|View full text |Cite
|
Sign up to set email alerts
|

Light environment change induces differential expression of guppy opsins in a multi‐generational evolution experiment

Abstract: Light environments critically impact species that rely on vision to survive and reproduce. Animal visual systems must accommodate changes in light that occur from minutes to years, yet the mechanistic basis of their response to spectral (color) changes is largely unknown. Here, we used a laboratory experiment where replicate guppy populations were kept under three different light environments for up to 8-12 generations to explore possible differences in the expression levels of nine guppy opsin genes. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 59 publications
(143 reference statements)
0
23
0
Order By: Relevance
“…The blue and blue‐green stimuli in our study stimulate both short and medium wavelength guppy cones. Kranz, Forgan et al () found no variation in short wavelength opsin expression across light environments but a decrease in medium wavelength opsin expression when fish were moved from the green and lilac environments to the same light environment as our test conditions (Kranz, Forgan et al, ). The relative expression of opsins has been shown to influence colour‐based behaviours (Smith, Ma, Soares, & Carleton, ), and thus, changes in the medium wavelength opsin expression of the fish may explain the decrease in pecking behaviour towards the blue and blue‐green stimuli.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The blue and blue‐green stimuli in our study stimulate both short and medium wavelength guppy cones. Kranz, Forgan et al () found no variation in short wavelength opsin expression across light environments but a decrease in medium wavelength opsin expression when fish were moved from the green and lilac environments to the same light environment as our test conditions (Kranz, Forgan et al, ). The relative expression of opsins has been shown to influence colour‐based behaviours (Smith, Ma, Soares, & Carleton, ), and thus, changes in the medium wavelength opsin expression of the fish may explain the decrease in pecking behaviour towards the blue and blue‐green stimuli.…”
Section: Discussionmentioning
confidence: 70%
“…The green stimulus was the only stimulus to be pecked at consistently across all treatments and replicates. The medium wavelength sensitive cones that are most highly stimulated by the green stimulus have the same expression across the three treatments as shown by Kranz, Forgan et al (2018b). There is also little difference in the position of the green stimulus in guppy tetrahedral colour space, indicating that this colour would be perceived similarly across all light treatments.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In other ecosystems, the introduction of artificial light at night can increase the duration of feeding times for visual predators, alter prey densities (e.g. Torres-Dowdall et al 2012;Kranz et al 2018;Ehlman, Martinez & Sih 2018) Gordon et al 2015). Changes in visual environments that might affect the efficacy of camouflage (e.g.…”
Section: F I G U R Ementioning
confidence: 99%
“…The irradiance spectra of these three light treatments were recorded by an Ocean Optics USB2000+ spectrometer calibrated for photon flux (visually relevant units, lmol photons m À1 s À1 nm À1 ) with a Li-Cor LI-1800-02 optical radiation calibrator. These three filter treatments were selected to be similar to different natural light environments (Endler, 1993b;Kranz et al, 2018). Green-F89 are more similar to forest shade natural light environments (Endler, 1993b).…”
Section: Light Environmentsmentioning
confidence: 99%